Principles and Applications of Generative and Cognitive Grammar: A Systematic Literature Riview - Aura Syalshabillah; Destina Kasriyati; Refika Andriani (EDUTREND: Journal of Emerging Issues and Trends in Education, 2024)
This study investigates the principles and applications of generative and cognitive grammar, focusing on their influence on language acquisition, literacy development, and second language learning. Spanning from 2020 to 2024, Databases such as Google Scholar and Crossref were used for the initial search, utilizing tools like Zotero and Publish or Perish. Keywords such as "generative grammar," "cognitive grammar," "applications," and "principles" An initial 1,200 articles were identified across Crossref and Google Scholar were employed. After applying rigorous inclusion and exclusion criteria, including the removal of duplicates and non-English articles, 35 articles were selected for in-depth analysis. Key findings highlight the positive impact of generative and cognitive grammar principles on engagement and outcomes in language learning, particularly for young and second language learners. Systematic and explicit instruction in these grammatical frameworks significantly improves syntactic and semantic skills. However, the review underscores the need for more empirical studies to establish standardized methodologies and assess long-term effects. The implications for practice, particularly in curriculum design and educational policy, are significant. Educators should integrate systematic instruction in generative and cognitive grammar into language learning programs, especially for young and second language learners. While grammatical skills are crucial for language development, instructional methods must be standardized to achieve lasting improvements. Additionally, the research indicates that early grammatical processing is a significant predictor of later language proficiency, emphasizing the need for early intervention and consistent instructional methods. Future research should continue exploring the most effective methods for teaching generative and cognitive grammar in diverse linguistic contexts, ensuring that all learners have the opportunity to develop strong language skills. This comprehensive understanding will aid in crafting educational policies and curricula that support robust language development across various learning environments.